Switchable dual- and single-wavelength mode-locked bismuth-doped fiber lasers at O-band - Ahmad, Harith; Nizamani, B.; Samion, M.Z.; Zulkifli, Mohd Zamani (Academic Press Inc., 2024)
In this work, we have demonstrated the switchable and tunable operation of mode-locked pulses at O-band. A 40 m silica-based bismuth-doped fiber (BDF) was used to provide a high gain with low losses in the O-band regime. The carbon nanotube (CNT) was used as a mode-locker, whereas the dual- and single-wavelength mode-locked pulses were achieved by including a tunable Mach-Zehnder filter (TMZF) to the BDF laser cavity. The laser operation was switched between dual- and single-wavelength operation by tuning the TMZF wavelength knob within the ring cavity. The operating wavelengths were at 1308.2 and 1328.5 nm for dual-wavelength mode-locked pulses. At the same time, the single wavelength mode-locked laser was tuned at three different operating wavelengths of 1316.3, 1328.5, and 1321.4 nm, with the 3-dB bandwidths of 3.3, 3.1 and 4.6 nm, and pulse durations of 790, 810 and 570 fs, respectively. The mode-locked laser remained stable from pump powers of 607 to 715 mW.